New secoiridoid ester of swertiamarin and secoxyloganic acid with hepatoprotective activity from Centaurium spicatum L. - Ahmed E. Allam; Alaa M. Nafady; Mohamed A. El-Shanawany; Fumide Takano; Tomihisa Ohta (GarVal Editorial Ltda., 2015)
Context: Centaurium spicatum (L.) Fritsch (Gentianaceae) is an annual herb occurring in Southern Europe and Northern Africa where it is used in traditional medicine for treatment of numerous illness. Aims: To isolate compounds from C. spicatum having hepatoprotective activity. Methods: Structure elucidation of the new compound was established on the basis of 1D and 2D NMR analyses including 1H-, 13C- NMR, DEPT-135 NMR, HMQC, HMBC and H- H HOHAHA experiments in addition to FAB+ and HRFAB+ Mass spectrometry. In vivo transaminases inhibition activity was carried out. Results: A new ester of swertiamarin and secoxyloganic acid (1) was isolated from C. spicatum in addition to its known components secoiridoids swertiamarin (2) and secoxyloganic acid (3). All tested secoiridoids have transaminases inhibition activity with different values for each compound 1, 2, 3 (86, 83, 81%) for SGOT and (96, 93, 91%) for SGPT, respectively. Conclusions: The new ester compound from C. spicatum has hepatoprotective activity over than its components.